Microscopic, elemental analysis, total organic carbon and Rock-Eval pyrolysis at DSDP Holes 64-479 and 64-480 - K E Peters; Bernd R T Simoneit (PANGAEA, 1982)
Geochemical analyses were carried out on Quaternary sediments from cores at Sites 479 and 480. The amount of organic matter indicates that these sediments have good to very good source-rock potential. Rock-Eval pyrolysis and microscopic examination show that many of the samples contain thermally immature, oil-prone, marine organic matter. Preliminary results show that Rock-Eval pyrolysis can distinguish oxic (bioturbated) and anoxic (laminated) organic facies in the cores. More than 10% of the organic carbon in these immature sediments is normally lost as hydrolysate during conventional acid treatment for the removal of carbonates. The protokerogen remaining after solvent extraction and acid maceration constitutes only a fraction of the total organic matter. Elemental analysis, pyrolysis, and vitrinite reflectance of the kerogenous residue show that it is considerably less oil prone than the total organic matter.
Supplement to: Peters, KE; Simoneit, BRT (1982): Rock-Eval pyrolysis of Quaternary sediments from Leg 64, Sites 479 and 480, Gulf of California. In: Curray, JR; Moore, DG; et al. (eds.), Initial Reports of the Deep Sea Drilling Project (U.S. Govt. Printing Office), 64, 925-931, https://doi.org/10.2973/dsdp.proc.64.138.1982